The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1096/fj.201701436r
|View full text |Cite
|
Sign up to set email alerts
|

REDD‐1 aggravates endotoxin‐induced inflammationVIAatypical NF‐κB activation

Abstract: Regulated in development and DNA damage responses 1 (REDD-1), an inhibitor of mammalian target of rapamycin (mTOR), is induced by various cell stressors, including LPS, a major player in the pathogenesis of endotoxemic shock. However, the pathologic role of REDD-1 in endotoxemia is largely unknown. We found that LPS increased REDD-1 expression, nuclear transcription factor-κB (NF-κB) activation, and inflammation and that these responses were suppressed by REDD-1 knockdown and in REDD-1 macrophages. REDD-1 over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 39 publications
8
51
0
Order By: Relevance
“…Redd1 expression is stimulated by cellular stress and influences a wide spectrum of cellular processes mainly through inhibition of mTOR signaling [ 22 25 ]. It was reported that Redd1 expression in the hippocampus increases markedly during normal aging, suggesting that Redd1 is an aging-associated factor [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redd1 expression is stimulated by cellular stress and influences a wide spectrum of cellular processes mainly through inhibition of mTOR signaling [ 22 25 ]. It was reported that Redd1 expression in the hippocampus increases markedly during normal aging, suggesting that Redd1 is an aging-associated factor [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regulated in development and DNA damage response-1 (Redd1), also known as DNA Damage-Inducible Transcript 4 (DDIT4), is a stress-response gene that is transcriptionally induced in various types of cells by stressful stimuli such as DNA damage, hypoxia, and energy deficits [ 20 , 21 ]. Redd1 is a potent inhibitor of mammalian Target of Rapamycin (mTOR) Complex-1 (mTORC1), and its expression influences a wide spectrum of cellular processes and biological functions, such as cell cycle, autophagy, energy homeostasis, and inflammation [ 22 25 ]. A regulatory role for Redd1 was reported in phenylephrine-induced cardiac hypertrophy [ 26 ] and myocardial ischemia/reperfusion injury [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the abnormal function of immune cells was involved in tumor resistance of pancreatic cancer. DDIT4 enhanced vascular inflammation and permeability in endotoxemia mice, leading to immune cell infiltration, systemic inflammation, caspase-3 activation, and apoptosis [ 27 ]. DDIT4 was related to the low level of reactive oxygen species of mitochondria in macrophages induced by IL-10 or hypoxia [ 28 ], and it inhibited the immune function of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial‐mediated regulation of autophagy has both a direct and indirect relationship with the onset of tumours and represents a key regulator of quality control in tumour cells. The outcome of activation of the autophagy pathway may differ depending on the stage of tumour development 45 . In this experiment, the relationship between NF‐κB and the activation of autophagy was examined by investigating the activation of LC3‐II protein.…”
Section: Discussionmentioning
confidence: 99%